INCREASING STUDENT RESPONSIBILITY THROUGH THE APPLICATION OF NUMBERED HEAD TOGETHER BASED ON STUDENT WORKSHEET - Sitorus, Monika Yosevin; Soesanto, Robert Harry (Nurul Jadid University, 2022)
Student responsibility is one of the attitudes that is expected to exist in students in carrying out learning. The attitude of responsibility will be seen in how students carry out their duties and obligations optimally the responsibility of students in learning is still a problem. In a study conducted on grade 8 students in a private school in the Tangerang area, it was found that student responsibility was low. This study uses a qualitative approach with a type of case study. The research results show that numbered head together model carries student-centered learning by applying 4 stages. The planning and numbering stage is the stage that supports the next stage. At the stage of thinking together, students have discussions in groups so that there is an increase in responsibility to be active in discussions. At this stage, students work on worksheets with focus and caution so that students’ responsibilities in doing assignments carefully also increase. In the answering stage, students will be randomly selected based on the numbers on their respective worksheets so that students are ready to be called because students are already responsible for completing the assigned tasks on time. This research is expected to provide real solutions to the problem of student responsibility.